Grape (Vitis vinifera L.) Seed Oil: A Functional Food from the Winemaking Industry - Martin, Maria E (Foods, 2020)
Wine production is an ancient human activity that generates several by-products, which include some constituents known for their potential in health care and for their role in the food or cosmetic industries. Any variety of grape (Vitis vinifera L.) contains nutrients and bioactive compounds available from their juice or solid parts. Grape seed extract has demonstrated many activities in disease prevention, such as antioxidant effects, which make it a potential source of nutraceuticals. Grape seed is a remarkable winery industry by-product due to the bioactivity of its constituents. Methods for recovery of oil from grape seeds have evolved to improve both the quantity and quality of the yield. Both the lipophilic and hydrophilic chemicals present in the oil of V. vinifera L. make this wine by-product a source of natural nutraceuticals. Food and non-food industries are becoming novel targets of oil obtained from grape seeds given its various properties. This review focuses on the advantages of grape seed oil intake in our diet regarding its chemical composition in industries not related to wine production and the economic and environmental impact of oil production.